Interactions among NGO, municipal government and users reduce the forest overexploitation, but does not stop it: A qualitative analysis on a community in the Bolivian Andes - Ayma-Romay, Ariel Isaías; Castro, Victoria (Bosque (Valdivia), 2017)
The role of interactions among local organizations to improve the institutions of the communities to use forests and avoid their overexploitation is still little understood. The objective of this study was to analyze the changes of institutions and modifications of the structure of the common forest from an Andean community from Bolivia, before, during and after these interactions. A qualitative analysis was carried out with the method of thematic content (deductive and inductive). Data were managed with the Weft QDA software. Our results showed that before interacting with local organizations, the community did not have institutions to regulate forest use; thus forests were overexploited. During the interaction, the rules to use the forest and control, monitoring and sanctions systems were created and implemented. The area and other structural attributes of the forest had been maintained, though the abundance old trees of Podocarpus glomeratus had decreased. After the interactions, the rules and control system continued; however the adaptation of rules, monitoring and sanction systems have been more difficult to sustain. Therefore, it is necessary to design policies to improve the collective action among communities and local organizations to reinforce the forest community management.